THE MAIN IDEAS OF THE OPTIMIZED PRODUCTION TECHNOLOGY (OPT) A METHOD OF PRODUCTION PLANNING - Majercak, Peter (Doprava a spoje, 2012)
The paper deals with a very actual topic about a method of production management in the enterprise. The authors describe very precisely the traditional method of production management in enterprises Theory of Constraints. Conclusion deals with design of progressive Optimized Production Technology (OPT), production planning system.